THE EFFECT OF THE PEER FEEDBACK TECHNIQUE ON STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE TEXTS - Olivia Fauzilah; Loly Novita; Destri Wahyuningsih (J-Shelves of Indragiri (JSI), 2026)
This research investigated the effect of the peer feedback technique on students’ writing achievement in descriptive texts at SMAN 2 Peranap. The study was conducted because many students still experienced difficulties in writing descriptive texts, such as limited vocabulary, grammatical errors, poor organization of ideas, and low confidence in expressing their thoughts in written form. Therefore, peer feedback was applied as an alternative teaching technique to improve students’ writing achievement through collaborative learning activities. This research used a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The population of the study consisted of 37 students from two classes and used total sampling technique. The experimental class was taught using peer feedback activities, while the control class received conventional teaching methods. The data were collected through pre-test and post-test writing assessments and analyzed using SPSS version 27, including normality testing, homogeneity testing, and Independent Samples T-Test analysis. The findings showed that the mean score of the experimental class increased from 40.18 in the pre-test to 74.09 in the post-test, while the control class improved from 40.87 to 58.52. The result of the homogeneity test showed that the data were homogeneous, with a significance value of 0.264, which was higher than 0.05. Furthermore, the Independent Samples T-Test showed that the Sig. (2-tailed) value was lower than 0.05, indicating a significant effect of the peer feedback technique on students’ writing achievement. Therefore, the alternative hypothesis (Hₐ) was accepted and the null hypothesis (H₀) was rejected. It can be concluded that the peer feedback technique significantly improved students’ writing achievement in descriptive texts at SMAN 2 Peranap.